Establish the training program of alternating current field measurement - level II according to SNT-TC-1A - Le , Duc Thinh; Ngo , Thi Kieu Oanh (Nuclear Science and Technology, 2021)
Alternating Current Field Measurement (ACFM) is a technique of the Electromagnetic method used to detect surface defects of metal materials. Currently, this technique is widely applied in the field of maintenance of Oil and Gas projects as an alternative to the Magnetic Particle Testing method. The establishment of ACFM training program according to Recommended Practice No. SNT-TC-1A of The American Society for Nondestructive Testing (ASNT) will increase the autonomy of the domestic testing human resources, especially advanced techniques. Based on documents and standards combined with the actual survey, training programs, training materials, question banks, examinations developed meet the requirements of international standards and in accordance with the conditions applied in Vietnam